Evaluation of a modified venous excess ultrasound (VExUS) protocol for estimation of venous congestion: a cohort study - Katharine C. Martin; Edward A. Gill; Ivor J. Douglas; August A. Longino (The Ultrasound Journal)
Abstract Background Understanding venous congestion is critical to the management of many illnesses, but assessing volume status can be challenging. The current gold standard for volume status assessment of right heart catheterization (RHC) is invasive, costly, and often unavailable. Venous Excess Ultrasound Score (VExUS) is a novel ultrasound protocol for to assessment of venous congestion using the inferior vena cava, hepatic, portal and renal veins. Though there is a much interest in the technique, the renal component of the exam is challenging to acquire. For this reason we aimed to see if a modified VExUS (mVExUS) excluding the kidney component performs similarly to traditional VExUS (tVExUS) for detecting elevated right atrial pressure (RAP) as measured by RHC. Methods A consecutive cohort of 95 patients undergoing RHC had VExUS exams before the procedure. Researchers compared the performance of tVExUS, mVExUS, and inferior vena cava (IVC) diameter in predicting RAP > 12 mmHg. Results The area under the curve (AUC) for detecting elevated RAP was similar for tVExUS (0.87) and mVExUS (0.85). Both methods achieved high sensitivity and specificity. Agreement between tVExUS and mVExUS scores was near-perfect (Cohen's Kappa = 0.85). Conclusion mVExUS may be as effective as tVExUS in identifying elevated RAP. This abbreviated version could improve efficiency and adoption of VExUS for assessing venous congestion. Further studies are needed in diverse patient populations.